The Gene Catalogue and Functional Analysis of the Gut Microbiome of Lions in Etosha National Park - Belger, Carl Warner (University of the Witwatersrand, Johannesburg, 2024)
Characterising the microbiomes of free-living mammals may aid conservation efforts, yet the gut microbiome of carnivores is underrepresented. This study represents the first description of the gut microbiome of free-living African lions (Panthera leo melanochaita). Faecal samples from 20 lions were collected in Etosha National Park, Namibia and microbial DNA was extracted. Samples were then whole genome sequenced, and classified using MetaPhlAn and Genome Taxonomy Database toolkit. The two most abundant bacterial genera in the lions’ gut microbiomes were Bacteroides (16.9%) and Phocaeicola (16.6%). Microbiome diversity was similar between the sexes and across seasons as assessed through Bray-Curtis dissimilarity and Shannon diversity index. The genus Clostridium_AH was more abundant in male lions (P = 0.007; d.f. = 22), while Aphodousia (P = 0.003; d.f. = 22) was more abundant in females. Lions captured in winter had a high abundance of Plesiomonas relative to those captured in summer (P = 0.008), whereas lions captured in summer a high abundance of Dysosmobacter (P = 0.038; d.f. = 22), Pelethomonas (P = 0.021; d.f. = 22), Metalachnospira (P = 0.033; d.f. = 22) and Clostridium Q (P = 0.012; d.f. = 22) compared to those captured in winter. Following various taxonomic classification approaches, a third of the reads (33.6%) present in the lion gut microbiome remained unclassified. We constructed 272 metagenome assembled genomes, from seven bacterial phyla, representing mostly new species which will contribute to understanding of the carnivore gut microbiome.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Microbial ecology; Gut microbiome; Metagenomics; Conservation biology; Host-microbe interactions; Functional genomics; Comparative microbiology; UCTD; SDG-15: Life on land; SDG-4: Quality education